Abelian and Tauberian results for the fractional Fourier and short-time Fourier transforms of distributions - Atanasova, Sanja; Maksimović, Snježana; Pilipović, Stevan (Informa UK Limited, 2023)
We introduce the fractional short-time Fourier transform in S′(R) and provide generalized asymptotics for the fractional Fourier and the short-time Fourier transforms within S′(R). Abelian- and Tauberian-type results are given.